P867 Cost-effectiveness and cost-only studies for Inflammatory Bowel Disease surgery: a scoping review. (30th January 2023) - Leeds, I; Prien, C; Dill-Macky, A; Li, H; Lincango, E; Holubar, S
Abstract: Background: Studies examining the relative cost-effectiveness of surgical procedures and surgery-related interventions for patients with inflammatory bowel disease (IBD) remain limited. This dearth of studies hampers decision-makers' assessment of surgery-related interventions for IBD patients. The purpose of this study was to conduct a scoping review of available literature for cost-effectiveness analyses of IBD-related surgery. Methods: We performed a comprehensive search of English-language articles in MEDLINE, EMBASE, Cochrane Reviews, and Scopus from each database's inception to May 1, 2022. Preplanned controlled vocabulary related to IBD and its subtypes, surgery, and measures of costs were used. We defined study selection criteria to include all IBD-related surgical interventions (including preoperative, intraoperative, and postoperative) in all age groups that also reported a measure of costs of care. Studies comparing medical versus surgical interventions for refractory IBD were excluded. All search findings were screened by two reviewers using titles, abstracts, and ultimately full-length manuscripts. Full screened studies were then extracted for study characteristics and findings to facilitate a qualitative synthesis of results. Results: We identified 1, 804 citations for screening and ultimately found 10 formal cost-effectiveness studies and 56 cost-only studies. Cost-effectiveness studies assessed intraoperative (50%) and postoperative interventions (50%) mostly in patients with Crohn's disease (60%). Topics included comparisons of surgical approach (50%), venous thromboembolism prophylaxis (30%), and surveillance for postoperative recurrence (2%). Of the cost-only studies, the majority focused on intraoperative interventions (89%), particularly in ulcerative colitis patients (60%). Areas of interest included costs associated with healthcare resource utilization during a surgery-related admission (89%), venous thromboembolism prophylaxis (4%), and others (7%). Pre-defined areas of interest with no reported interventions included IBD-specific roles of Enhanced Recovery After Surgery interventions such as alvimopan, robotic surgery, timing to surgery, surgical therapies for perianal disease, pediatric Crohn's Disease, and genetic testing. Conclusion: A scoping review found minimal literature using cost-effectiveness techniques to inform IBD-related surgical care. There are many more cost-only than cost-effectiveness studies related to these clinical topics. This asymmetry highlights immediately available opportunities for broadening the use of cost-effectiveness analysis of IBD-related surgical interventions.